Integrating Social Sciences in Computer Applications: Enhancing User Experience, Ethical Development, And Social Interaction Dynamics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This abstract highlights the various ways in which social sciences can be applied in the context of computer applications. It emphasizes the importance of understanding user behavior in UX design, using social science research methods for data analytics, and incorporating social sciences in HCI to improve usability. It also discusses the role of social sciences in addressing ethical concerns in AI development and exploring social interactions through social computing. The abstract concludes by emphasizing the overall impact of integrating social sciences into computer applications, leading to more user-centered and responsible technologies.